KEMAMPUAN PRODUKSI BIOGAS PADA DIGESTER BERBAHAN FIBERGLASS BERUKURAN 120 L - Mustaqim .; Ahmad Farid; Sandra Sugara (Engineering : Jurnal Bidang Teknik, 2011)
Research capability of the digester biogas production made from fiberglass sized 120 liter conducted with the aim of knowing severa l stages of the process to be able process cow manure into biogas and to know the process of making biogas producing from cow manure tools in use : pipe saws, electric weld, grunding machine, hammer, gauges, sricssors, while the material in use : jembung fiberglass 120 liter, pipe ½ inch, pipe 4 inch, L dan T pipe form, L pipe form 4 inch, glue pipe, stop value ½ inch, stop value ¼ inch, rubber hose, iron pipe ¼ inch. Research methods and data analysis by colleeting data on biogas conducted to determine the variation in the form of a mixture, determine the gas pressure gauge on the ang biogas flame test and cost data for tool-making technigue producting biogas from low manure. Reresult is a processed cow manure into biogas with a variation of a mixture of cow manure with water (15 Kg-  10 L), (15 Kg-15 L), (15 Kg-  20 L) from experiment of flame can be proction with the variation (15 Kg-  15 L) with the longfire flaming is 34 seconds. The shaped of unit processing cow waste become biogas with cost which needed Rp 403.000,-Key word : biogas, digester, fiberglass